A Randomized Feeding Trial of Iron-Biofortified Beans in School Children in Mexico - Finkelstein, Julia L.; Mehta, Saurabh; Villalpando, Salvador; Mundo-Rosas, Veronica; Luna, Sarah V.; Rahn, Maike; Shamah-Levy, Teresa; Beebe, Stephen E.; Haas, Jere D. (MDPI, 2019)
Iron deficiency is a major public health problem worldwide, with the highest burden among children. The objective of this randomized efficacy feeding trial was to determine the effects of consuming iron-biofortified beans (Fe-Beans) on the iron status in children, compared to control beans (Control-Beans). A cluster-randomized trial of biofortified beans (Phaseolus vulgaris L.), bred to enhance iron content, was conducted over 6 months. The participants were school-aged children (n = 574; 5–12 years), attending 20 rural public boarding schools in the Mexican state of Oaxaca. Double-blind randomization was conducted at the school level; 20 schools were randomized to receive either Fe-Beans (n = 10 schools, n = 304 students) or Control-Beans (n = 10 schools, n = 366 students). School administrators, children, and research and laboratory staff were blinded to the intervention group. Iron status (hemoglobin (Hb), serum ferritin (SF), soluble transferrin receptor (sTfR), total body iron (TBI), inflammatory biomarkers C-reactive protein (CRP) and α-1-acid glycoprotein (AGP)), and anthropometric indices for individuals were evaluated at the enrollment and at the end of the trial. The hemoglobin concentrations were adjusted for altitude, and anemia was defined in accordance with age-specific World Health Organization (WHO) criteria (i.e., Hb <115 g/L for <12 years and Hb <120 g/L for ≥12 years). Serum ferritin concentrations were adjusted for inflammation using BRINDA methods, and iron deficiency was defined as serum ferritin at less than 15.0 µg/L. Total body iron was calculated using Cook’s equation. Mixed models were used to examine the effects of Fe-Beans on hematological outcomes, compared to Control-Beans, adjusting for the baseline indicator, with school as a random effect. An analysis was conducted in 10 schools (n = 269 students) in the Fe-Beans group and in 10 schools (n = 305 students) in the Control-Beans group that completed the follow-up. At baseline, 17.8% of the children were anemic and 11.3% were iron deficient (15.9%, BRINDA-adjusted). A total of 6.3% of children had elevated CRP (>5.0 mg/L), and 11.6% had elevated AGP (>1.0 g/L) concentrations at baseline. During the 104 days when feeding was monitored, the total mean individual iron intake from the study beans (Fe-bean group) was 504 mg (IQR: 352, 616) over 68 mean feeding days, and 295 mg (IQR: 197, 341) over 67 mean feeding days in the control group (p < 0.01). During the cluster-randomized efficacy trial, indicators of iron status, including hemoglobin, serum ferritin, soluble transferrin receptor, and total body iron concentrations improved from the baseline to endline (6 months) in both the intervention and control groups. However, Fe-Beans did not significantly improve the iron status indicators, compared to Control-Beans. Similarly, there were no significant effects of Fe-Beans on dichotomous outcomes, including anemia and iron deficiency, compared to Control-Beans. In this 6-month cluster-randomized efficacy trial of iron-biofortified beans in school children in Mexico, indicators of iron status improved in both the intervention and control groups. However, there were no significant effects of Fe-Beans on iron biomarkers, compared to Control-Beans. This trial was registered at clinicaltrials.gov as NCT03835377.